Coraline A Closer Look at Studio LAIKA's Stop-Motion Witchcraft - Mihailova, Mihaela (Animation: Key Films/Filmmakers, 2021)
Coraline (Henry Selick, 2009) is stop-motion studio LAIKA's feature-length debut based on the popular children's novel by British author Neil Gaiman. Heralding a revival in global interest in stop-motion animation, the film is both an international cultural phenomenon and a breakthrough moment in the technological evolution of the craft. This open access collection brings together an international group of practitioners and scholars to examine Coraline's place in animation history and culture, dissect its politics, and unpack its role in the technological and aesthetic development of its medium. More broadly, it celebrates stop motion as a unique and enduring artform while embracing its capacity to evolve in response to cultural, political, and technological changes, as well as shifting critical and audience demands. Divided into three sections, this volume's chapters situate Coraline within an interconnected network of historical, industrial, discursive, theoretical, and cultural contexts. They place the film in conversation with the medium's aesthetic and technological history, broader global intellectual and political traditions, and questions of animation reception and spectatorship. In doing so, they invite recognition - and appreciation - of the fact that Coraline occupies many liminal spaces at once. It straddles the boundary between children's entertainment and traditional 'adult' genres, such as horror and thriller. It complicates a seemingly straight(forward) depiction of normative family life with gestures of queer resistance. Finally, it marks a pivotal point in stop-motion animation's digital turn. Following the film's recent tenth anniversary, the time is right to revisit its production history, evaluate its cultural and industry impact, and celebrate its legacy as contemporary stop-motion cinema's gifted child. As the first book-length academic study of this contemporary animation classic, this volume serves as an authoritative introduction and a primary reference on the film for scholars, students, practitioners, and animation fans. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com.